ORGANIZATIONAL COMMITMENT MEDIATES THE EFFECT OF WORK CULTURE ON BAWASLU EMPLOYEE PERFORMANCE - Perial Darma; Defrizal (International Journal of Multidisciplinary Reseach, 2026)
Employee performance is a strategic determinant of public-sector accountability, particularly in an election supervisory institution that requires integrity, professionalism, and timely service. This study examined the effects of work culture on employee performance, both directly and through organizational commitment, among employees of the Election Supervisory Agency (Bawaslu) of North Lampung Regency. A quantitative associative survey was conducted using a census of all 35 employees. Data were collected through questionnaires supported by observation and interviews, then analyzed using validity and reliability tests, classical assumption testing, simple and multiple linear regression, t tests, F tests, coefficients of determination, and the Sobel test. The results showed that work culture significantly affected organizational commitment (B = 0.656; t = 10.237; p < 0.001), organizational commitment significantly affected performance (B = 1.014; t = 11.496; p < 0.001), and work culture significantly affected performance (B = 0.796; t = 14.986; p < 0.001). The joint model explained 89.9% of performance variance. The Sobel statistic of 8.150 (p < 0.001) confirmed a significant mediating role of organizational commitment. Strengthening consistent work values, employee involvement, fair recognition, and cross-unit collaboration is therefore essential for improving institutional performance.